A sociedade de risco e a noção de cidadania: desafios para a educação científica e tecnológica - Pietrocola, Maurício (2019)
Ulrich Beck, in a work published in 1986 and entitled "risk society", which states that modern social life is faced with new forms of danger produced by herself and that challenge humanity. This implies that living in a "risk society" would be to assume a calculating attitude towards the possibilities of action, positive and negative, with which we are continually confronted. This confrontation impacts both existence on an individual and global level. In this paper we intend to examine how this evaluation of social modernity impacts the notion of citizenship and suspends the perspectives contained in the CTS and Scientific Literacy approaches and advances the discussion on the challenges of reflective modern scientific education